Development of Forehand and Beckhand Spin Training Equipment in Table Tennis - Nopiadi Nopiadi; Zusyah Porja Daryanto; Nevi Hardika (Jurnal Pendidikan Olah Raga, 2026)
This study aims to produce a mechanical training tool for table tennis forehand and backhand spin techniques that are valid, practical, and effective for Junior High School Extracurricular athletes consisting of SMPN throughout Teluk Kermat District. The research method used is Research and Development (R&D) by adopting the Brog and Gall model development procedure (Research and Information Collecting, Planning, Develop Preliminary Form of Product, Preliminary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision, Operational Field Testing, Final Product Revision, Dissemination and Implementation). The research sample consisted of 30 adolescent athletes aged 12-15 years selected using a purposive sampling technique. Data collection instruments included a feasibility assessment questionnaire for experts and a skill test instrument using the Target Grid Assessment technique to measure athletes' motor performance before and after the intervention. The results of the research from the expert validation team showed a feasibility percentage of 88% and from the trainer practitioners at 91%, both of which were included in the very feasible criteria. The results of the effectiveness test showed an average N-gain score of 0.65, which confirms that the level of effectiveness of the training model is in the moderate or effective category, with an increase in the distribution of scores from the initial average (pre-test) of 63 to 86 in the final evaluation (post-test). The conclusion of this study is that the integration of mechanical training tools designed through the structure is proven to be very valid and effective in improving the quality and accuracy of spin technique stability in young athletes. This study aims to produce a mechanical training tool for table tennis forehand and backhand spin techniques that are valid, practical, and effective for Junior High School Extracurricular athletes (SMP) consisting of SMPN throughout Teluk Kermat District.The research method used is Research and Development (R&D) by adopting the Brog and Gall model development procedure (Research and Information Collecting, Planning, Develop Preliminary Form of Product, Preliminary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision, Operational Field Testing, Final Product Revision, Dissemination and Implementation). The research sample consisted of 30 adolescent athletes aged 12-15 years selected using a purposive sampling technique. Data collection instruments included a feasibility assessment questionnaire for experts and a skills test instrument using the Target Grid Assessment technique to measure athletes' motor performance before and after the intervention. The research results from the expert validation team showed a feasibility percentage of 88% and from the trainer practitioners of 91%, both included in the very feasible criteria. The effectiveness test results showed an average N-gain score of 0.65, which confirms that the level of effectiveness of the training model is in the moderate or effective category, with an increase in the distribution of scores from an initial average (pre-test) of 63 to 86 in the final evaluation (post-test). The conclusion of this study is that the integration of mechanical training tools designed through the structure is proven to be very valid and effective in improving the quality and accuracy of spin technique stability in young athletes.